Sri Lanka : Staff Report for the 2001 Article IV Consultation and Request for Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2001)
In concluding the 1999 Article IV Consultation with Sri Lanka on October 13, 1999, Executive Directors had stressed the need to address the longstanding economic problems that are impeding Sri Lanka's growth. Macroeconomic management and structural reform have been complicated by a difficult political situation. Against this background, the 2001 Article IV Cconsultation discussions have focused on ways to address the serious immediate economic problems and to resume progress toward medium-term fiscal consolidation in the 2001 budget.